Long-term spatial dynamics of jaguars in a high-density population - Bart J. Harmsen; Rebecca J. Foster (PLoS ONE, 2025)
We assessed the socio-spatial dynamics of a jaguar population over 15 years using camera-trap data from Belize. Using ~4,000 independent detections of male jaguars, we documented and quantified range shifts, overlap, and interactions between males. Additionally, ~ 700 independent detections of females allowed us to investigate interactions between the sexes. Using the distance between activity centres, we assessed the variation in space use within and between males. Male ranges were not stable: activity centres shifted from one year to the next, with a mean maximum distance moved of 8 km per individual between any two years (SD = ± 6 km, n = 371). Overall, we found no evidence of exclusive territoriality. Male jaguars overlapped extensively with one another: males shared, on average, half of their detected range with at least one other male, per year (Volume of Intersect, kernel overlap); while their activity centres lay within 2 km of at least one other male. Close encounters (two individuals at the same location within 24h) were most common between males whose activity centres were ≤ 4 km apart. We found that close encounters between prime males (3-7y) and old males (≥ 8y) occurred less frequently than expected, suggesting avoidance of stronger competitors by the physically weaker, older age class. Notably, old males also had fewer close encounters than expected with females; potentially having reduced access to females because they were avoiding areas frequented by prime males. However, we found no clear evidence of males monopolising females, as females tended to associate with more than one male during the short time windows when they were detected on trails. Overall these results are consistent with a system of scramble competition among males in which overlapping and shifting ranges result from searching for receptive females that are distributed sparsely and unevenly in space and time.